The Hypoglycemic and Renal Protection Properties of Crocin via Oxidative Stress-Regulated NF-κB Signaling in db/db Mice - Qiu, Ye; Jiang, Xue; Liu, Danping; Deng, Zichun; Hu, Weiwei; Li, Zhiping; Li, Yuxin (Frontiers in Pharmacology, 2020)
Background As the main ingredient of Crocus sativus L. (Iridaceae) extract, crocin- I (CR) has been reported to show various pharmacological activities. The aim of this study was to investigate the hypoglycemic and renal protection properties of CR in db/db mice. Methods Eight-week-old db/db mice were treated with metformin (Met) (100 mg/kg) and CR (50 mg/kg) for eight weeks. Results CR treatment showed hypoglycemic functions indicated by reduced bodyweight, food and water intake, plasma glucose, and serum levels of glycated hemoglobin A1c. Additionally, the CR group showed increased serum levels of insulin and pyruvate kinase, hypolipidemic functions indicated by the suppressed levels of total cholesterol and triglyceride, and enhanced levels of high-density lipoprotein cholesterol, which are also indicators of hypoglycemic functions. The renal protection function of CR was demonstrated by its protection of renal structures and its regulation of potential indicators of nephropathy. The anti-oxidation and anti-inflammation effects of CR were verified by enzyme-linked immunosorbent assay. In the kidneys of db/db mice, CR decreased the expression of phospho-IκBα and phospho-nuclear factor-κB (NF-κB), whereas it enhanced the expression of nuclear respiratory factor 2, manganese superoxide dismutase 1, heme oxygenase-1, and catalase. Conclusions The anti-diabetic and anti-diabetic nephritic effects of CR were related to its modulation of oxidative stress-mediated NF-κB signaling.